Continental-scale decreases in shorebird populations in Australia - Clemens, Roberts; Rogers, Danny I.; Hansen, Birgita D.; Gosbell, Ken; Minton, Clive D. T.; Straw, Phil; Bamford, Mike; Woehler, Eric J.; Milton, David A.; Weston, Michael A.; Venables, Bill; Wellet, Dan; et al. (Emu, 2016)
Decreases in shorebird populations are increasingly evident worldwide, especially in the East Asian–Australasian Flyway (EAAF). To arrest these declines, it is important to understand the scale of both the problem and the solutions. We analysed an expansive Australian citizen-science dataset, spanning the period 1973 to 2014, to explore factors related to differences in trends among shorebird populations in wetlands throughout Australia. Of seven resident Australian shorebird species, the four inland species exhibited continental decreases, whereas the three coastal species did not. Decreases in inland resident shorebirds were related to changes in availability of water at non-tidal wetlands, suggesting that degradation of wetlands in Australia’s interior is playing a role in these declines. For migratory shorebirds, the analyses revealed continental decreases in abundance in 12 of 19 species, and decreases in 17 of 19 in the southern half of Australia over the past 15 years. Many trends were strongly associated with continental gradients in latitude or longitude, suggesting some large-scale patterns in the decreases, with steeper declines often evident in southern Australia. After accounting for this effect, local variables did not explain variation in migratory shorebird trends between sites. Our results are consistent with other studies indicating that decreases in migratory shorebird populations in the EAAF are most likely being driven primarily by factors outside Australia. This reinforces the need for urgent overseas conservation actions. However, substantially heterogeneous trends within Australia, combined with declines of inland resident shorebirds indicate effective management of Australian shorebird habitat remains important.